The Differences in Conjunctival Impression Cytology Profile, Interleukin-6 Levels in Tears, and Stages of Dry Eye Between Anophthalmic Socket and Contralateral Healthy Eye) - Nur Aulia; Suliati Paduppai; Halimah Pagarra; Junaedi Sirajuddin; Rina Masadah; Rusdina Bte Ladju (Jurnal Penelitian Pendidikan IPA, 2026)
Dry eye is one of the symptoms that can be suffered by anophthalmic socket eye, which is related to changes in the conjunctival epithelium and inflammatory processes in the anophthalmic socket eye. This study aims to determine differences in the degree of conjunctival impression cytology, tear pro-inflammatory cytokine interleukin-6 (IL-6), and degree of a dry eye between the anophthalmic socket eye and the contralateral healthy eye. This research is a cross-sectional study. Seventeen patients with anophthalmic socket eyes underwent conjunctival impression cytology examination, assessed tear levels of the pro-inflammatory cytokine IL-6, Schirmer test examination, and filled in the Dry Eye Questioner-5 (DEQ-5). The examination was performed simultaneously on the anophthalmic socket eye and the contralateral healthy eye. This study showed a significant difference in conjunctival impression cytokine (p= 0.004) and a significant difference in tear pro-inflammatory cytokine IL-6 levels (p= 0.014). There was no significant difference (p=0.319) in the results of the Schirmer 1 test, but there was a significant difference in the Schirmer 2 test (p=0.0047). There is a significant difference in the value of the DEQ-5 questionnaire (p = 0.003). There were significant differences in conjunctival impression cytology, tear pro-inflammatory cytokine IL-6, and degree of the dry eye between the anophthalmic socket eye and the contralateral healthy eye. Therefore, it is necessary to administer artificial tear drops to each patient with anophthalmic socket as a preventive measure for dry eye in the anophthalmic socket.